Hepatocellular Carcinoma Mimicking Neuroendocrine Tumor Metastasis on 68Ga-DOTATATE PET/CT. (April 2019) - Ulaner, Gary A.; Bodei, Lisa
Abstract : Abstract: 68 Ga-DOTATATE is a radiolabeled somatostatin analog used for the detection and characterization of somatostatin receptor (SSR)–overexpressing tumors, particularly well-differentiated neuroendocrine tumors. We present a case of a 65-year-old man with well-differentiated pancreatic neuroendocrine tumor post–Whipple surgery and a new liver lesion on CT. 68 Ga-DOTATATE PET/CT was performed for SSR characterization and restaging, which demonstrated the lesion to be intensely SSR positive and interpreted as a neuroendocrine metastasis. However, subsequent pathology proved the lesion to be a hepatocellular carcinoma. This case adds hepatocellular carcinoma as a potentially DOTATATE-avid malignancy to be considered in the differential diagnoses of SSR-positive liver lesions.